Scale-dependent cloud enhancement from land restoration in West African drylands - Jessica Ruijsch; Christopher M. Taylor; Ronald W. A. Hutjes; Adriaan J. Teuling (Communications Earth & Environment)
Abstract Land restoration projects, including reforestation and area protection, are being implemented across African drylands such as the Sahel. In addition to biodiversity, livelihood and carbon sequestration benefits, restoration can also affect the local climate through land-atmosphere interaction. Yet, it remains unknown to what extent dryland restoration can affect cloud cover development and, ultimately, precipitation. Here, we use twenty years of high-resolution data from the Meteosat Second Generation satellite to study the impact of land restoration on cloud development in West African drylands. Results show that cloud cover frequency and convective initiation are higher above vegetated areas, particularly during the start and end of the wet seasons. Furthermore, we find a more pronounced cloud cover enhancement over protected areas larger than 121 km2, suggesting a scale-dependent relationship between project size and cloud cover development.